2000
DOI: 10.1095/biolreprod62.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transforming Growth Factor-α and the Epidermal Growth Factor Receptor in Embryonic Rat Testis Development1

Abstract: Embryonic testis development requires the morphogenesis of cords and growth of all cell populations to allow organ formation. It is anticipated that coordination of the growth and differentiation of various cell types involves locally produced growth factors. The current study was an investigation of the hypothesis that transforming growth factor-alpha (TGF-alpha) is involved in regulating embryonic testis growth. TGF-alpha has previously been shown to function in the postnatal testis. TGF-alpha and other memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 54 publications
3
53
0
2
Order By: Relevance
“…Scale bars: 100 μm in a,f; 50 μm in b-e,g-j. Kluin et al, 1984;Levine et al, 2000). Together, these data suggest that the influence of the Np95 cKO is restricted to germ cells in the testis.…”
Section: Research Articlementioning
confidence: 69%
“…Scale bars: 100 μm in a,f; 50 μm in b-e,g-j. Kluin et al, 1984;Levine et al, 2000). Together, these data suggest that the influence of the Np95 cKO is restricted to germ cells in the testis.…”
Section: Research Articlementioning
confidence: 69%
“…Most important, the influence of technology for female infertility treatment such as ICSI complicates the results of male infertility treatment (effect-modifying factor) [55]. spermatogenesis [38][39][40][41][42][43][44]. We found that transactivation of the EGF receptor (EGFR), a tyrosine kinase type receptor through the activation of LHR, a G protein coupled receptor, occurred both in MA-10 cells [45] and rat Leydig cell primary culture [46] after hCG stimulation.…”
Section: Fsh Therapy For Spermatogenic Disordersmentioning
confidence: 98%
“…TGF-a). [24] or neurotropin receptors such as low affinity neurotropin receptor (p75/LNGFR) [25]. However, besides the general knowledge that growth factors participate in different cellular compartments of the testis, little is known about the codistribution of TGF-a and VEGF in seminiferous tubuli.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor (EGF)/TGF-a is a family of growth factors that has attracted attention as putative regulators of embryonic [48] and testicular [24] development. Earlier results [49] supported by more recent findings [50] indicate that EGF/TGF-a family members are also directly involved in the regulation of spermatogenesis.…”
mentioning
confidence: 99%